The coupled cooling effect of ventilation and spray in the deep-buried high-temperature tunnel - Guoliang Zhang; Zhongan Jiang; Hui Wang; Xingpeng Jing; Mingli Si; Fabin Zeng; Bin Yang; Xiangdong Yang; Rui Feng (Case Studies in Thermal Engineering, 2023)
The utilization of ventilation and spray cooling technology is becoming increasingly popular in high-temperature workplaces due to its convenience and environmental friendliness. To investigate the coupled cooling effect of ventilation and spray in a construction tunnel, we established a droplet evaporation model under convective heat transfer conditions by combining the convective heat transfer theory and the droplet heat and mass transfer model. Based on this model, the study focused on the energy change of droplet evaporation in a moving medium by using numerical simulation in the context of a railroad construction tunnel. The material of the droplets used in the study was water. According to the simulation and field measurement results, it was obtained that, firstly, increased air volume of the tunnel and reduced airflow temperature could make the convective heat exchange stronger between the airflow and the wall. Secondly, the particle size of droplets formed by spraying was mainly 30–40 μm in the tunnel. A part of the droplets was evaporated in the high-temperature environment, and another part was trapped by the rock wall and ground. Third, adopting the coupled cooling method of ventilation and spray, the temperature and humidity fields in the tunnel changed significantly, and a low-temperature and high-humidity zone appeared near the nozzle. At the same time, the evaporation rate of droplets increased, the heat index of the workplace decreased, and the cooling effect was effective. Therefore, the coupled cooling method of ventilation and spray can effectively improve the thermal environment in high-temperature construction tunnels and enhance the thermal comfort of personnel. This study serves as a reference for the parameters and cooling effect of ventilation and spray cooling systems in construction sites.